Overexpression and activation of EGFR and VEGFR2 in medullary thyroid carcinomas is related to metastasis - Rodríguez-Antona, Cristina; Pallares, Judith; Montero-Conde, Cristina; Inglada-Pérez, Lucia; Castelblanco, Esmeralda; Landa, Iñigo; Leskelä, Susanna; Leandro-García, Luis J; López-Jiménez, Elena; Letón, Rocío; Cascón, Alberto; Lerma, Enrique; et al. (Endocrine-related cancer, 2010)
Therapeutic options for patients with metastatic medullary thyroid carcinoma (MTC) are limited due to lack of effective treatments. Thus, there is a need to thoroughly characterize the pathways of molecular pathogenesis and to identify potential targets for therapy in MTC. Since epidermal growth factor receptor (EGFR) seems to play a crucial role for RET activation, a key feature of MTCs, and several promising EGFR/vascular endothelial growth factor receptor 2 (VEGFR2)-targeted drugs have been developed, the present study was designed to investigate whether these proteins are altered in MTCs. We used a well-characterized series of 153 MTCs to evaluate EGFR activation by sequencing and FISH analysis, and to perform EGFR and VEGFR2 immunohistochemistry. EGFR tyrosine kinase domain mutations were not a feature of MTCs; however, EGFR polysomy and a strong EGFR expression were detected in 15 and 13% of the tumors respectively. Interestingly, EGFR was significantly overexpressed in metastases compared with primary tumors (35 vs 9%, P=0.002). We also studied whether specific RET mutations were associated with EGFR status, and found a decrease in EGFR polysomies (P=0.006) and a tendency towards lower EGFR expression for the most aggressive RET mutations (918, 883). Concerning VEGFR2, metastasis showed a higher expression than primary tumors (P=2.8×10−8). In this first study investigating the relationship between EGFR, RET, and VEGFR2 in a large MTC series, we found an activation of EGFR and VEGFR2 in metastasis, using both independent and matched primary/metastasis samples. This suggests that some MTC patients may benefit from existing anti-EGFR/VEFGR2 therapies, although additional preclinical and clinical evidence is needed.